2022
DOI: 10.1155/2022/6013474
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effectiveness and Safety between High-Power Short-Duration Ablation and Conventional Ablation for Atrial Fibrillation: A Systematic Review and Meta-Analysis

Abstract: Aim. We aimed to evaluate the effectiveness and safety between high-power short-duration (HPSD) radiofrequency ablation (RFA) and conventional RFA in patients with atrial fibrillation (AF). Methods. Studies comparing HPSD and traditional applications in patients undergoing initial catheter ablation for atrial fibrillation from inception through December 2021 were searched on Pubmed, Medline, Cochrane, and Clinicaltrials.gov. Results. The meta-analysis included seventeen studies with a total of 4934 patients. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The high-power short-duration (HPSD) ablation strategy comprises the use of higher RFCA power (≥ 40 W) and a shorter duration (5-15 s) of each RF energy application, and HPSD ablation results in larger lesion diameters and smaller lesion depths compared to conventional (20-35 W, 10-30 s) applications 28 . Highpower ablation was previously associated with better procedural effectiveness than conventional RFCA with low power 29 . Based on these studies, in our study, the ndings demonstrated the effectiveness of SRI with a high power of 40-45 w in restoring sinus rhythm, and it was also superior to CPVI + MPOBI.…”
Section: Discussionmentioning
confidence: 99%
“…The high-power short-duration (HPSD) ablation strategy comprises the use of higher RFCA power (≥ 40 W) and a shorter duration (5-15 s) of each RF energy application, and HPSD ablation results in larger lesion diameters and smaller lesion depths compared to conventional (20-35 W, 10-30 s) applications 28 . Highpower ablation was previously associated with better procedural effectiveness than conventional RFCA with low power 29 . Based on these studies, in our study, the ndings demonstrated the effectiveness of SRI with a high power of 40-45 w in restoring sinus rhythm, and it was also superior to CPVI + MPOBI.…”
Section: Discussionmentioning
confidence: 99%
“…These MA have included anywhere between 7 to 22 studies with 1013 to 4934 patients in their pooled analysis. Seven of these MA have demonstrated improved FFA with HPSD in their primary analysis when both persistent and paroxysmal AF patients are included 6,7,9–11,13,14 . Only one of these MA conducted a sub‐group analysis comparing outcomes stratified by AF type, be it paroxysmal or persistent AF.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are 9 MA comparing the utility of HPSD versus LPLD for AF ablation in the literature. [6][7][8][9][10][11][12][13][14] These MA have included anywhere between 7 to 22 studies with 1013 to 4934 patients in their pooled analysis. Seven of these MA have demonstrated improved FFA with HPSD in their primary analysis when both persistent and paroxysmal AF patients are included.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations